Cardiopulmonary Resuscitation of Asystolic Newborn Lambs Prior to Umbilical Cord Clamping; the Timing of Cord Clamping Matters! - Polglase, Graeme R.; Schmölzer, Georg M.; Roberts, Calum T.; Blank, Douglas A.; Badurdeen, Shiraz; Crossley, Kelly J.; Miller, Suzanne L.; Stojanovska, Vanesa; Galinsky, Robert; Kluckow, Martin; Gill, Andrew W.; Hooper, Stuart B. (Frontiers in Physiology, 2020)
Background: Current guidelines recommend immediate umbilical cord clamping (UCC) for newborns requiring chest compressions. Physiologically-based cord clamping (PBCC), defined as delaying UCC until after lung aeration, has advantages over immediate UCC in mildly asphyxiated newborns, but its efficacy in asystolic newborns requiring CC is unknown. The aim of this study was to compare the cardiovascular response to CCs given prior to, or after UCC in asystolic near-term lambs. Methods: Umbilical, carotid, pulmonary and femoral arterial flows and pressures as well as systemic and cerebral oxygenation were measured in near term sheep fetuses (139±2 (SD) days gestation). Fetal asphyxia was induced until asystole ensued whereupon lambs received ventilation and CC before (PBCC; n=16) or after (n=10) UCC. Epinephrine was administered 1 min after ventilation onset and in 3-minute intervals thereafter. The PBCC group was further separated into UCC at either 1 min (PBCC1) or 10 minutes (PBCC10) after return of spontaneous circulation (ROSC). Lambs were maintained for a further 30 minutes after ROSC. Results: The duration of chest compressions received and number of epinephrine doses required to obtain ROSC was similar between groups. After ROSC, we found no physiological benefits if UCC was delayed for 1 min compared to ICC. However, if UCC was delayed for 10 min after ROSC, we found significant reductions in post-asphyxial rebound hypertension, cerebral blood flow and cerebral oxygenation. The prevention of the post-asphyxial rebound hypertension in the PBCC10 group occurred due to the contribution of the placental circulation to a low peripheral resistance. As a result, left and right ventricular output continued to perfuse the placenta, evidenced by reduced mean pulmonary blood flow, persistence of right-to-left shunting across the ductus arteriosus and persistence of umbilical arterial and venous blood flows. Conclusion: It is possible to obtain ROSC after CC while the umbilical cord remains intact. There were no adverse effects of PBCC compared to ICC, however, the physiological changes observed after ROSC in the ICC and early PBCC groups may result in additional cerebral injury. Prolonging UCC after ROSC may provide significant physiological benefits that may reduce the risk of harm to the cerebral circulation.